Situational Factors Influencing Employee Theft in Supermarket Outlets: A Survey of Kisumu City, Kenya - Kibet, Rebecca J. (2020)
Employees' theft is an act of stealing, use, or misuse of an employer's asset without his or her consent. Despite the security surveillance measures taken by the supermarket retail outlets, these businesses are yet to have any significant reduction in the theft cases in the supermarkets. The study aimed to establish the effects of situational factors on employees' theft in the supermarket outlets within Kisumu City, Kenya. The objectives of the study were: to assess the effect of prevailing opportunity to steal on employees' theft, to examine the contribution of organizational values and culture to employees' theft, to establish how employees' attributes contribute to theft and to determine the effect of job dissatisfaction on employees' theft in the supermarkets within Kisumu City. The study adopted a cross-sectional qualitative research design. The study was informed by Rational Choice Theory developed by Siegel and McCormick, 2006, and Equity Theory of Employee Motivation established by Adams. In this study, a qualitative survey design was adopted. A convenient sampling technique was used to sample 10 managers, 10 cashiers, and 10 subordinate staff from 10 supermarket outlets within Kisumu City out of the target population of 400 employees. The analyzed demographic data were presented in frequency tables and charts while qualitative data was analyzed thematically. The study revealed that the availability of opportunity to steal is one of the main reasons why employees working in supermarkets indulge in workplace theft. This occurs due to the use of weak monitoring systems to curb theft-related cases by supermarket managers. Besides, the study established that staff who steal from the workplace do not recognize the formal organizational values and practices imposed by the management. As a result, poor organization values and cultural practices have a meaningful effect on the employees in the supermarkets thus influence employees’ theft. This, therefore, means that organizational values guide the employees on what is right or wrong and what is most important in life, hence greatly controls their behavior in the organizations. Moreover, employees with negative personal attributes for instance were more likely inclined towards engaging in criminal behavior such as theft than those who did not. The study recommends that future researchers should conduct a comparative study on the causes of job dissatisfaction and how it contributes to employees' theft. Lastly, the study recommends that further research should be conducted on the overall perception of the workplace theft by employees across the different organizations. Key Words: employees, theft, supermarkets, business, opportunity, organization values DOI: 10.7176/RHSS/10-18-09 Publication date:September 30th 202